Swinging Thuribles in Early Byzantine Churches in the Holy Land - Vitto, Fanny (Actual Problems of Theory and History of Art, 2016)
The use of swinging thuribles for incense burning is a familiar scene in the Eastern Orthodox and Roman Catholic churches. The practice of incense burning in religious ceremonies predates Christianity by thousands of years, and the Old Testament, for example, contains numerous references to it. As early as the 4th century A.D., literary sources described the practice of burning incense during the church services in the Holy Land. Several examples of bronze bowls with no lid, suspended by three chains, have been discovered in Early Byzantine churches in the Eastern Mediterranean or are depicted on mosaics of contemporaneous churches in Ravenna and in present-day Jordan. Unlike the Catholic Church, the Eastern Church continued using uncovered swinging thuribles for many centuries.
Keywords: swinging thuribles; frankincense; Early Byzantine churches; Holy Land